THE CONCEPT OF "BIRDS" IN THE PHRASEOLOGICAL LANDSCAPE (BASED ON ENGLISH MATERIALS) - Usenova Gulmira Abillayevna; Rustamova Melhriniso Rashid qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation This article explores the concept of "birds" in English phraseology, analyzing how avian imagery is embedded in idioms, proverbs, and fixed expressions. Birds serve as powerful symbols in language, reflecting human emotions, behaviors, and cultural beliefs. The study categorizes bird-related phrases, examines their semantic functions, and  discusses  their  metaphorical  meanings.  By  reviewing  linguistic  and  cultural sources,  the  article  highlights  the  universality  and  diversity  of  bird  symbolism  in English.